Improving the Relationship of Medicaid Home and Community-Based Services Home Care Aides and Clients Through Health Interviewing. (July 2020) - Danilovich, Margaret; Diaz, Laura; Boyken, Lara; Eisenstein, Amy; Johnson, Rebecca
Medicaid home and community-based services (HCBS) care plans should be person-centered, yet there is little research on how to ascertain this information in practice. The purpose of this study was to investigate the feasibility of a home care aide (HCA)–led health interview with clients during usual HCBS. We provided interview training, and HCAs ( n = 21) conducted five interviews with one client each using a card sort methodology to elicit client care preferences. HCAs audio-recorded interviews and photographed card sorts for analysis. We used a mixed-methods approach of semistructured interviews and focus groups with clients and HCAs to evaluate the health interviewing experience and client surveys of Your Health Orientation, Willingness to Communicate, and PROMIS (Patient-Reported Outcomes Measurement Information System) global health and HCA surveys of the Active Empathetic Listening Scale. We used t tests to investigate changes in survey outcomes pre and post interviews. Results show HCAs can conduct health interviews, and doing so contributes new knowledge on client preferences for care. Clients desire HCAs who provide empathy, compassion, and motivation, and HCAs felt interviewing clients helped them to better understand their care recipient's needs.